2006
DOI: 10.1073/pnas.0607822103
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid fisetin promotes ERK-dependent long-term potentiation and enhances memory

Abstract: Small molecules that activate signaling pathways used by neurotrophic factors could be useful for treating CNS disorders. Here we show that the flavonoid fisetin activates ERK and induces cAMP response element-binding protein (CREB) phosphorylation in rat hippocampal slices, facilitates long-term potentiation in rat hippocampal slices, and enhances object recognition in mice. Together, these data demonstrate that the natural product fisetin can facilitate long-term memory, and therefore it may be useful for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
206
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 281 publications
(214 citation statements)
references
References 37 publications
6
206
0
2
Order By: Relevance
“…Furthermore, following a single intraperitoneal injection, fisetin was detected in the brains of rats and this correlated with a significant reduction in cerebral damage in a stroke model [73]. Similarly, we have seen significant protection in a rabbit stroke model following intravenous injection of fisetin [58] and we found that oral administration of fisetin could enhance learning and memory in mice [57]. Thus, fisetin is able to affect neuronal function in vivo.…”
Section: Metabolism Of Fisetinsupporting
confidence: 65%
See 4 more Smart Citations
“…Furthermore, following a single intraperitoneal injection, fisetin was detected in the brains of rats and this correlated with a significant reduction in cerebral damage in a stroke model [73]. Similarly, we have seen significant protection in a rabbit stroke model following intravenous injection of fisetin [58] and we found that oral administration of fisetin could enhance learning and memory in mice [57]. Thus, fisetin is able to affect neuronal function in vivo.…”
Section: Metabolism Of Fisetinsupporting
confidence: 65%
“…Rolipram also had no effect on basal synaptic responses in rat hippocampal slices but facilitated LTP induced by a weak tetanic stimulus in a manner very similar to fisetin [4]. However, in contrast to rolipram, fisetin did not increase cAMP levels in the hippocampal slices [57].…”
Section: Fisetin Can Enhance Cognitive Functionmentioning
confidence: 82%
See 3 more Smart Citations